THE INFLUENCE OF WORK ENVIRONMENT, WORK CULTURE, AND WORK ROTATION ON EMPLOYEE PRODUCTIVITY AT HUMAN RESOURCES DEVELOPMENT CENTRE KEMENDAGRI YOGYAKARTA - Herlina, Sri; Kaloeti, Ade Kristianus (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2024)
The study aimed to examine the relationship between the work environment, work culture, work rotation, and employee productivity at the Human Resources Development Centre (PPSDM) Kemendagri Regional Yogyakarta. The research method used in this study was quantitative descriptive research. The study population comprised all employees working at the Human Resources Development Centre Kemendagri Yogyakarta, while the sample consisted of 100 respondents, including 83 civil servants (PNS) and 17 non-civil servant government employees. The results of the study showed that work environment, work culture, and work rotation had a positive and significant effect on employee productivity at the Human Resources Development Centre Kemendagri Yogyakarta, based on the results of simple linear regression analysis and t-test.